The 1978/79 performance of major business enterprises in Nigeria - Nigerian Institute of Social and Economic Research (NISER) (Ibadan: Nigerian Institute of Social and Economic Research (NISER), 1979)
This book reflects the achievements and problems of Nigerian business enterprises in 1978/79.
A Service of The Business Monitoring Programme of the Business & Industrial Consultancy Division, Nigerian Institute of Social and Economic Research (NISER).
rpm 12/02/2019
Loans
Keywords: Business Enterprises; Nigeria